EFFECTIVENESS OF MEDIATION AS A TYPOLOGY OF CIVIL DISPUTE SETTLEMENT (ADR) AT DISTRICT COURT OF BALI - I Ketut Tjukup; I Putu Rasmadi Arsha Putra; Dewa Gede Pradnya Yustiawan (Kertha Wicaksana, 2018)
Mediation has been a typology of civil dispute settlement through negotiation process to obtain agreement from the parties assisted by mediator. The Court implements mediation which is a process of civil disputes settlement that must be taken as an instrument to fulfill the four purposes of the Supreme Court, such as addressing the problem of the accumulation of cases; faster and cheaper dispute resolution; expanding access for the parties to a sense of justice; and strengthening and maximizing the function of the courts in dispute settlement. The focus of this study lies in the investigation of the extent to which effective mediation is applied as an alternative of civil disputes settlement at the District Court of Bali. The method used is empirical law research method. The nature of this research is descriptive. There are two types of data, namely primary data and secondary data with the location of research is the District Court in Bali Province. Data collection was done by using interview techniques; Data processing and analysis were carried out by applying qualitative data analysis method. The result of the research shows that the implementation of mediation in the District Court in Bali has been in accordance with the legislation and has been capable of decomposing cases. However, obstacles in the implemention are still other significant problems that need concern of resolution. The obstacles are those relating to legal substance, legal structure and legal culture.